Potent anti-nociceptive and anti-inflammatory effects of methanol fraction of Otostegia persica extract and its components - Z. Tofighi; S.N. Ostad; S. Khezrrahdoost; H. Salehizadeh; N. Yassa (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Otostegia persica (Labiatae) is an endemic plant of Iran and is used for its anti-inflammatory properties in folk medicine of Sistan and Baluchestan province. The aim of the present study was to investigate the anti-nociceptive and anti-inflammatory effects of O. Persica different fractions and identification of the natural compounds from the most active fraction. Methods: Total extract of O. Persica was fractionated with petroleum ether (PE), chloroform (CL), ethyl acetate (EA), n-butanol (BU) and methanol (ME). The analgesic activities of different fractions were determined by formalin test. Then, activity of effective fractions was investigated on carrageenan-induced paw edema assay. Finally, the compounds of effective fraction were isolated and their structures were elucidated. Results: Anti-nociceptive activity of EA and BU fractions (100 mg/kg) and ME fraction (100 and 200 mg/kg) demonstrated significant difference with normal saline during the second phase of the formalin test. ME fraction showed higher analgesic effects in comparison to indomethacin (p0.05). Vicenin-2 and isorhamnetin-3-O-glucoside were elucidated from ME as the effective anti-inflammatory fraction. Conclusion: It was concluded that the existence of flavonoids in O. persica extract could play an important role for its anti-nociceptive and anti-inflammatory effects similar to various non-steroidal anti-inflammatory drugs (NSAIDS) and inhibitors of nitric oxide synthase (NOS).